MENINGKATKAN AKTIVITAS PESERTA DIDIK DALAM PEMBELAJARAN IPS MELALUI METODE PEMBELAJARAN COOPERATIVE SCRIPT DI KELAS VIII B SMP NEGERI 2 AMUNTAI SELATAN - Lathifah Lathifah (JURNAL SOCIUS, 2014)
In teaching-learning activity, it is necessary to incrcase the Students’ Activities. In practice, however, the teacher often do not realize that there are still a lot of what they do, even inhibiting the students being more active. As one of the efforts to increse the students’ activities in IPS teaching-learning, it is necessary to use the Cooperative Script method. To be able to increase the students’  activities. To answer the above questions, this research is designed as a Classroom Action Research (PTK) method, implemented in SMPN 2 Amuntai Selatan, Hulu Sungai Utara regency. There are 12 students in class VIII B, consists of 6 boys and 6 girls. The research uses the  qualitative and quantitative techniques in collecting data.Kata Kunci : Increasing activity, Social Studies,and  Cooperative Script.